Impact of soil texture and salt type on salt precipitation and evaporation under different hydraulic conditions. Issue 11 (24th November 2022) - Li, Xinhu; Guo, Min; Wang, Hongchao
Abstract: Salt precipitation and evaporation in porous media is an important research topic. However, several aspects remain controversial; notably, whether efflorescence inhibits evaporation in wet soil, the influence of soil texture on salt crust formation and the effect of sulphate precipitation on evaporation under changing hydraulic conditions. Therefore, this study investigates the influence of salt type (NaCl and Na2 SO4 ) and soil texture (sandy soil, sandy loam and silt loam) on salt precipitation and evaporation under different hydraulic conditions (with and without fixed groundwater). Our results demonstrated that a NaCl salt crust strongly inhibited evaporation, even from wet soil (with groundwater), owing to its denser salt structure, which inhibited fluid flow. Moreover, the salt crust pattern differed based on soil texture. Relatively thin, flat and uniform salt crusts were developed in finer soils (silt loam), with greater evaporation resistance, whereas thick and rough salt crusts were developed in coarser soil (sandy soil), with less evaporation resistance. Na2 SO4 was precipitated as subflorescence in drying soil, whereas wet soils exhibited a mixed salt precipitation pattern including both efflorescence and subflorescence. Notably, evaporation was primarily inhibited by efflorescence, rather than subflorescence. Our research provides novel insights into the dynamics of salt precipitation and evaporation in natural soils. Abstract : Salt crust formation differed with soil texture, i.e., thinner, flatter and more uniform salt crusts with larger evaporation resistance developed in finer soils (silty loam), whereas thicker, rougher salt crusts with less evaporation resistance developed in coarser soil (sand) (fig a). Na2 SO4 was precipitated as subflorescence in drying soil, but as efflorescence plus subflorescence in wet soils (fig b). Evaporation was predominantly inhibited by efflorescence.